Fuelwood Consumption and Participation in Community Forestry in India - Bandyopadhyay, Sushenjit (World Bank, Washington, D.C., 2013)
Decentralized forest management is an important policy issue in India and elsewhere. Yet there are few careful studies of the impacts of community forestry. The authors try to fill this gap by analyzing National Sample Survey data from 524 villages in five states in India. Their analysis seeks to answer two key questions: (1) Who participates in community forestry and what are the determinants of participation? (2) What is the impact of participation on household fuelwood consumption? The authors find that proximity to forests, leadership, and fuelwood dependence are significant factors in explaining village participation in community forestry. Household participation is strongly correlated with scarcity, a result that has implications for a recent policy to expand community forestry from degraded to less degraded forests. The authors' most important findings are that fuelwood consumption and participation are linked, and household participation has a significant positive impact on consumption. However, the presence of a village level forestry institution does not have a direct effect.